Review of Recent Progress on Silicon Nitride-Based Photonic Integrated Circuits - Tarun Sharma (IEEE Access, 2020)
Silicon photonic devices used in the photonics industry over the past three decades have helped in realizing large-scale photonic integrated circuits. Silicon nitride (Si3N4) is another CMOS-compatible platform that provides several advantages such as low loss, high optical power tolerance, and broad spectral operation band from visible to infrared wavelengths. Recently, the combination of Si3N4 waveguide technology with silicon photonics and III-V materials has opened up new areas in on-chip applications. Researchers in the field are primarily focusing on its applications such as on-chip gas sensing, nonlinear optical signal processing, and label-free biosensors based on photonic integrated circuits. In this review paper, we discuss Si3N4 material-based platforms for a variety of applications with devices ranging from passive to active and hybrid photonic devices.